Legal prerequisites of private detective activity in the Republic of Kazakhstan (Journal of actual problems of jurisprudence, 2022)
The article deals with the issues of balancing the interests of the individual and the state, most clearly manifested in the criminal process, by the example of the implementation of the principle of privacy, issues of private detective activity in the Republic of Kazakhstan, issues of improving legislation on professional secrets, which are the most important mechanisms designed to protect the right to privacy of citizens. The legal analysis of guarantees of observance of constitutional rights of citizens in the implementation of private detective activities in criminal proceedings is carried out.In this regard, the authors actualize the need for further improvement of legislation defining the legal regime of privacy in criminal proceedings; the implementation of private detective activities in the Republic of Kazakhstan. Also relevant are: the essence, importance and role of the measures of criminal procedural coercion applied by the state, in particular by the bodies of criminal prosecution, which amounts to ensuring state legality and law and order; the principle of inviolability of private life as the fundamental and guiding principle of the entire criminal process of the Republic of Kazakhstan. For this purpose, the work examines the norms of the legislation of the Republic of Kazakhstan, the range of homogeneous public relations regulated by them on the implementation of individual rights and freedoms in criminal proceedings, the practice of law enforcement on the issues under consideration in the Republic of Kazakhstan, on the basis of which proposals are being developed to improve legislation; theoretical and legal foundations of private detective activity as an activity related to the protection of the legitimate rights and interests of the individual of the Republic of Kazakhstan.In the study of the questions posed, a logical, formal – legal, analytical, as well as functional method is used, revealing the qualitative characteristics of the subject of research, allowing to determine the essence of the institution under study, the possibility of regulatory impact of constitutional and sectoral legislation on the state of law and order in the Republic of Kazakhstan. In the scientific analysis undertaken by the authors, the principles of complexity and consistency are consistently implemented and productively combined, which made it possible to more fully, scientifically actualize the issues of improving criminal procedural capabilities for the realization of individual rights and freedoms.As a result of the study, it was determined that the participation of a private detective in the criminal process will serve as a guarantee of the protection of the rights and legitimate interests of an individual only if the rules and procedures provided for by law for obtaining and researching information about a person's private life are observed.Keywords: human rights, private life, the principle of privacy, criminal proceedings, detective work, detective.